2019
DOI: 10.3389/fphar.2019.00209
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Pharmacogenetic Factors Contributing to Platelet Function Recovery After Single Dose of Ticagrelor in Healthy Subjects

Abstract: Objectives: This study aimed to elucidate the contribution of candidate single nucleotide polymorphisms (SNPs) related to pharmacokinetics on the recovery of platelet function after single dose of ticagrelor was orally administered to healthy Chinese subjects.Methods: The pharmacokinetic profiles of ticagrelor and its metabolite AR-C124910XX (M8), and the platelet aggregation (PA), were assessed after 180 mg of single-dose ticagrelor was orally administered to 51 healthy Chinese subjects. Effects of CYP2C19*2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
2
14
1
Order By: Relevance
“…Nevertheless, concurrent with a previous study, the observed ABCB1 variants, such as rs2235048, rs2235047, rs1045642, rs2235013, and rs2235033, were not associated with the PK of ticagrelor (Teng, 2015). In addition, the remaining CYP2C9, CYP2B6, UGT2B7, and SLCO1B1 polymorphisms had no effect on the PK of ticagrelor and its metabolite AR-C124910XX, which is consistent with previous findings (Zhou et al, 2011;Zhu et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Nevertheless, concurrent with a previous study, the observed ABCB1 variants, such as rs2235048, rs2235047, rs1045642, rs2235013, and rs2235033, were not associated with the PK of ticagrelor (Teng, 2015). In addition, the remaining CYP2C9, CYP2B6, UGT2B7, and SLCO1B1 polymorphisms had no effect on the PK of ticagrelor and its metabolite AR-C124910XX, which is consistent with previous findings (Zhou et al, 2011;Zhu et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…CYP2C19*2 and CYP2C19p3 appeared to be the most common alleles in the Chinese population. A previous study reported that CYP2C19*3 G/G carriers had a higher T max than G/A carriers after a single dose of ticagrelor (Zhu et al, 2019). In our study, CYP2C19*2 had no effect on the PK of ticagrelor.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The clinical application of genetic testing to optimize therapeutic strategies lacks sufficient evidence that understanding of the genetic determinants of ticagrelor. 16 …”
Section: Introductionmentioning
confidence: 99%
“…The clinical application of genetic testing to optimize therapeutic strategies lacks sufficient evidence that understanding of the genetic determinants of ticagrelor. 16 Therefore, a prospective experiment involving 100 Chinese patients with the percutaneous coronary intervention was designed. SNP and clinical characteristics were associated to antiplatelet response and bleeding event after ticagrelor treatment.…”
Section: Introductionmentioning
confidence: 99%